Pollen tube development of crosses among Brazilian apple cultivars - Albuquerque Junior, Celso Lopes de; Denardi, Frederico; Dantas, Adriana Cibele de Mesquita; Nodari, Rubens Onofre (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this study was to evaluate pollen tube growth in crosses between Brazilian apple cultivars. Artificial pollination was carried out among cultivars that bloom at the same time (34 crosses). Pollination was done on three stigmas in each of the ten emasculated flowers per crossing. Fluorescence was used to visualize pollen tube growth in flowers collected 120 hours after pollination. In most of the cross-pollinations, high percentage of pollen tubes reached the ovary. The visualization of pollen tube growth by the fluorescence technique permitted the separation of compatible or partial compatible crosses from the incompatible ones.